2021
DOI: 10.47742/ijbssr.v2n2p3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Social Media Marketing, Electronic Word of Mouth and Consumer Engagement to Brand Loyalty in Indonesia Grab Company

Abstract: This study aims to analyze social media marketing, electronic word of mouth, and consumer attachment to brand loyalty in Grab Indonesia. The research design used is quantitative research with a causal approach that examines the effect of exogenous variables (social media marketing, electronic word of mouth, and consumer attachment) on endogenous variables (brand loyalty). The population in this study were consumers of social media followers (Instagram) grab with an infinite number, therefore sampling was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
1
4
0
5
Order By: Relevance
“…Namely, customer engagement can positively predict brand loyalty. These results are in line with research by (Tuti & Sulistia, 2022), (Widodo & Febrianti, 2021), and (Bismoaziiz et al, 2021), which state that customer engagement can positively predict brand loyalty. According to (Tuti & Sulistia, 2022), a brand must increase customer involvement so that consumers can increase their desire to order and ultimately increase brand loyalty.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Namely, customer engagement can positively predict brand loyalty. These results are in line with research by (Tuti & Sulistia, 2022), (Widodo & Febrianti, 2021), and (Bismoaziiz et al, 2021), which state that customer engagement can positively predict brand loyalty. According to (Tuti & Sulistia, 2022), a brand must increase customer involvement so that consumers can increase their desire to order and ultimately increase brand loyalty.…”
Section: Discussionsupporting
confidence: 91%
“…Besides that, (Tuti & Sulistia, 2022), who researched online stores, showed that customer engagement significantly and positively affects brand loyalty. Other research conducted by (Bismoaziiz et al, 2021) shows that customer engagement has a positive and significant effect on the brand loyalty of online transportation.…”
Section: Relationship Between Customer Engagement and Brand Loyaltymentioning
confidence: 89%
“…EWOM and social media content are crucial components of social media marketing to increase engagement [22,23]. Research in this field is still limited and challenging to comprehend despite researchers' increased attention to content marketing and engagement [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The use of social media allows individuals to obtain information that is relevant to them quickly, and the impact of the adoption of this media on the world of marketing is very significant, turning it into a more efficient promotional tool than traditional media (Horbinski, 2019).Apart from that, the use of social media has also influenced people's lifestyles and shopping interests. Indonesian society, which is said to have a high level of self-confidence in its consumer behaviour, is the focus of this research (Bismoaziiz et al, 2021). The fast food industry is also an interesting phenomenon in this context, with increasing demand for practical food with minimal additives (Sari & Basit, 2020).…”
mentioning
confidence: 99%
“…Apart from that, the use of social media has also influenced people's lifestyles and shopping interests. Indonesian society, which is said to have a high level of self-confidence in its consumer behaviour, is the focus of this research (Bismoaziiz et al, 2021). The fast food industry is also an interesting phenomenon in this context, with increasing demand for practical food with minimal additives (Sari & Basit, 2020).…”
mentioning
confidence: 99%